BESHKENT BOTIQLIGI MEZOZOY YOTQIZIQLARI STRATIGRAFIK KESIMINING SEYSMIK XUSUSIYATLARI BO‘YICHA TAHLIL QILISH - Xayriddinov Bahodir Baxtiyor o‘g‘li; Muxtorov Nodirbek Murodjon o‘g‘li; O‘rolova Ma’mura Shavkat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. In order to confirm the petrophysical properties and non-homogeneity of the rocks in the research carried out in the areas studied in the article, the analysis and interpretation of the results of the inter-site UCHN seismological survey was carried out and analyzed based on the time sections taken from the areas of the research area.